M2a Macrophage-Secreted CHI3L1 Promotes Extracellular Matrix Metabolic Imbalances via Activation of IL-13Rα2/MAPK Pathway in Rat Intervertebral Disc Degeneration - Li, Long; Wei, Kang; Ding, Yifan; Ahati, Paerxiati; Xu, Haoran; Fang, Huang; Wang, Huan (Frontiers in Immunology, 2021)
The accumulation of macrophages in degenerated discs is a common phenomenon. However, the roles and mechanisms of M2a macrophages in intervertebral disc degeneration (IDD) have not been illuminated. This study investigated the expression of the M2a macrophage marker (CD206) in human and rat intervertebral disc tissues by immunohistochemistry. To explore the roles of M2a macrophages in IDD, nucleus pulposus (NP) cells were co-cultured with M2a macrophages in vitro. To clarify whether the CHI3L1 protein mediates the effect of M2a macrophages on NP cells, siRNA was used to knock down CHI3L1 transcription. To elucidate the underlying mechanisms, NP cells were incubated with recombinant CHI3L1 proteins, then subjected to western blotting analysis of the IL-13Ra2 receptor and MAPK pathway. CD206-positive cells were detected in degenerated human and rat intervertebral disc tissues. Notably, M2a macrophages promoted the expression of catabolism genes (MMP-3 and MMP-9) and suppressed the expression of anabolism genes (aggrecan and collagen II) in NP cells. These effects were abrogated by CHI3L1 knockdown in M2a macrophages. Exposure to recombinant CHI3L1 promoted an extracellular matrix metabolic imbalance in NP cells via the IL-13Ra2 receptor, along with activation of the ERK and JNK MAPK signaling pathways. This study elucidated the roles of M2a macrophages in IDD and identified potential mechanisms for these effects.